2013
DOI: 10.1155/2013/684035
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Risk and Past Exposure to Emissions from a Large Steel Plant

Abstract: We studied the spatial distribution of cancer incidence rates around a large steel plant and its association with historical exposure. The study population was close to 600,000. The incidence data was collected for 1995–2006. From historical emission data the air pollution concentrations for polycyclic aromatic hydrocarbons (PAH) and metals were modelled. Data were analyzed using Bayesian hierarchical Poisson regression models. The standardized incidence ratio (SIR) for lung cancer was up to 40% higher than av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Findings from epidemiological investigations in high risk areas near iron foundries are inconsistent. Two analytical studies [ 20 , 21 ] that adjusted for smoking and a descriptive study [ 22 ] that adjusted for socioeconomic status showed that living near an iron foundry was not a risk factor for lung cancer incidence or mortality. Descriptive studies that did not adjust for smoking displayed an increased risk of lung cancer living near iron foundries [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from epidemiological investigations in high risk areas near iron foundries are inconsistent. Two analytical studies [ 20 , 21 ] that adjusted for smoking and a descriptive study [ 22 ] that adjusted for socioeconomic status showed that living near an iron foundry was not a risk factor for lung cancer incidence or mortality. Descriptive studies that did not adjust for smoking displayed an increased risk of lung cancer living near iron foundries [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Forastiere et al (1994) found no excess lung cancer in conjunction with duration of employment as traffic police. Breugelmans et al (2013) found no increased lung cancer associated with past PAH or Cd emissions from a large steel factory. Kachuri et al (2017) reported that both male and female Canadian agricultural workers had statistically significantly lower lung cancer risks, with RRs from 0.58 to 0.75.…”
Section: Occupational Studiesmentioning
confidence: 75%
“…One of the secondary clusters in the Mifflin County revealed the highest risk ratio of lung cancer compared to the other four clusters, associated with the lowest per capita income (median = 16.51%) and the highest percent poverty (29.3% below poverty line), and the poorest physical and mental health (17% and 19.3%, respectively). The primary economic activities in this area in the past, included the manufacturing of steel [ 23 ], machinery [ 24 ], and textiles [ 25 ], which are often accompanied by adverse environmental impacts and may have contributed to the increased risk of lung cancer. Radon, a known risk factor for lung cancer [ 26 ], is also shown to have higher levels in the Mifflin County For example, zip codes in the Mifflin County area were discovered to have high radon levels in homes in the past (e.g., the average radon concentrations were 5.2 pCi/L (first floor) and 11.2 pCi/L (basement) in 17,044, 16.7 pCi/L (first floor), and 20.4 pCi/L (basement) in 17,084).…”
Section: Discussionmentioning
confidence: 99%